Faktor yang Mempengaruhi Nilai Tukar Rupiah Terhadap Dolar Amerika, Euro dan Poundsterling - Wanda Khamidah; Retno Sugiharti (Ecoplan, 2022)
The currency exchange rate is a macro indicator that reflects the strength of the economy as a result of the global economy. With the existence of currency exchange rates, it can facilitate international trade transactions with currency agreements that will be used by the two countries. The exchange rate system used in Indonesia is a free-floating exchange rate system since 1997, all of which are left to the market. This study aims to analyze the effect of the money supply, inflation and foreign exchange reserves on the rupiah exchange rate of against the US dollar (USD), euro (EUR), and pound sterling or Great Britain Pound (GBP). The ECM (Error Correction Model) the analysis method is the method used in this study. The results of the research that has been carried out are both in the long term and in the low term, the money supply, inflation and foreign exchange reserves have a significant influence on the exchange rate of the rupiah against the US dollar (IDR/USD). The money supply and foreign exchange reserves and in the short term have a significant effect on the rupiah exchange rate against the euro (IDR/EUR), while only the money supply in the long term has a significant effect on the rupiah exchange rate in the euro (IDR/EUR). Foreign exchange reserves in the short term have a significant effect on the rupiah exchange rate against the pound sterling (IDR/GBP), while only the money supply in a long term has a significant effect on the rupiah exchange rate against the pound sterling (IDR/GBP).